Prevalensi infeksi hiv pada pemakai napza di Surabaya tahun 1999/2000 = Prevalence of hiv infection among drug users in Surabaya 1999/2000 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Nowdays, the number 6f drug users is increasing. Drug abuse is regarded as one of the main cause of the HIV/ AIDS spread. The objectives of the study are to estimate prevalence of HIV infection among the drug users in Surabaya municipality and to identify the risk factors. The research is a cross sectional study with quantitative and qualitative apporach. Interviews were conducted to 102 drug users. Subjects were selected using a simple random sampling. Indepth interviews were carried out to have more detailed information about variables of this study. The independent variables are age, sex, educational level, occupation, marriage status, types of drug, methods of drug use and sexual behavior. From the researsh, it is found that prevalence of HIV infection among drug users is 6,86%. The 2X2 tables show that the methods of drug use have significant association to HIV infection (p < 0,05). The multiple logistic regression showed that HIV infection was associated with injecting drug use (p = 0, 0279, OR=11,2726). Drug users have higher risk at HIV infection. The methods of drug use are associated with the prevalence of HIV infection. Injecting drug use was significantly a risk factor for HIV infection.